1995
DOI: 10.1002/chir.530070506
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselectivity of the carbonyl reduction of dolasetron in rats, dogs, and humans

Abstract: The initial step in the metabolism of dolasetron or MDL 73,147EF [(2 alpha, 6 alpha, 8 alpha, 9a beta)-octahydro-3-oxo-2,6-methano-2H- quinolizin-8-yl 1H-indol-3-carboxylate, monomethanesulfonate] is the reduction of the prochiral carbonyl group to give a chiral secondary alcohol "reduced dolasetron." An HPLC method, using a chiral column to separate reduced dolasetron enantiomers, has been developed and used to measure enantiomers in urine of rats, dogs, and humans after dolasetron administration. In all case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…This raises the issue of stereochemical metabolic coverage across species in the drug development process. Differences in the stereochemistry of reduction have been noted between human and animal metabolism for some compounds (Benedetti et al, 1991(Benedetti et al, , 1993Dow and Berg, 1995;Vickers et al, 1993;Weil et al, 1989;Wsól et al, 1998a). Thus, the occurrence of this metabolic pathway requires that a decision be made about the timing for development of a chiral assay for the metabolite.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…This raises the issue of stereochemical metabolic coverage across species in the drug development process. Differences in the stereochemistry of reduction have been noted between human and animal metabolism for some compounds (Benedetti et al, 1991(Benedetti et al, , 1993Dow and Berg, 1995;Vickers et al, 1993;Weil et al, 1989;Wsól et al, 1998a). Thus, the occurrence of this metabolic pathway requires that a decision be made about the timing for development of a chiral assay for the metabolite.…”
Section: Resultsmentioning
confidence: 95%
“…The outcome of pharmacokinetic studies with this derivative of benfluron has not yet been reported. In a different example, carbonyl reduction was the mode of activation of the prodrug dolasteron (Anzemet) to the antiemetic, hydrodolasetron (Dow and Berg, 1995). When administered orally, only the reduced dolasetron was quantifiable in plasma; when administered intravenously, the parent drug was rapidly cleared from plasma and could be measured for only 2 to 4 hr after dosing (Boxenbaum et al, 1992(Boxenbaum et al, , 1993Shah et al, 1995).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The reduced alcohol formed by this conversion, hydrodolasetron, contains a chiral carbon center. In a study that measured the enantiomers of hydrodolasetron in urine of rats, dogs, and humans following intravenous and oral administration of dolasetron, the conversion of achiral dolasetron to chiral hydrodolasetron was found to be stereoselective, with the R(+ ) enantiomer accounting for the majority (\ 90%) of hydrodolasetron excreted in human urine [11]. Therefore, a final objective was to determine the pharmacokinetic profiles of R(+ ) and S(− )-hydrodolasetron following both intravenous and oral administration of dolasetron based on plasma concentration determinations, as well as urinary excretion profiles.…”
Section: Introductionmentioning
confidence: 98%
“…4 Both stereoselectivity and stereospecificity of reduction has been observed with warfarin and its analogs, 5 ketotifen, oxonortriptyline, 6 and dolasetron. 7 Monitoring the stereospecificity of reduction enabled the detection of the participation of two different enzyme systems in the reduction of 4-phenyl-3-butyn-2-one 8 and haloperidol. 9 Many nonsteroidal antiinflammatory drugs (NSAID) belong to important groups of chiral drugs.…”
mentioning
confidence: 99%